Tissue engineering at the dentin-pulp interface using human treated dentin scaffolds conditioned with DMP1 or BMP2 plasmid DNA-carrying calcium phosphate nanoparticles. (15th March 2023) - Machla, F; Sokolova, V; Platania, V; Prymak, O; Kostka, K; Kruse, B; Agrymakis, M; Pasadaki, S; Kritis, A; Alpantaki, K; Vidaki, M; Chatzinikolaidou, M; et al.
Abstract: Hard dental tissue pathologies, such as caries, are conventionally managed through replacement by tooth-colored inert biomaterials. Tissue engineering provides novel treatment approaches to regenerate lost dental tissues based on bioactive materials and/or signaling molecules. While regeneration in the form of reparative dentin (osteo-dentin) is feasible, the recapitulation of the tubular microstructure of ortho-dentin and its special features is sidelined. This study characterized in vitro, and in vivo human EDTA-treated, freeze-dried dentin matrices (HTFD scaffolds) conditioned with calcium phosphate nanoparticles (NPs) bearing plasmids encoding dentinogenesis-inducing factors (pBMP2/NPs or pDMP1/NPs). The uptake and transfection efficiency of the synthesized NPs on dental pulp stem cells (DPSCs) increased in a concentration- and time-dependent manner, as evaluated qualitatively by confocal laser microscopy and transmission electron microscopy, and quantitatively by flow cytometry, while, in parallel, cell viability decreased. HTFD scaffolds conditioned with the optimal transfectability-to-viability concentration at 4 µg Ca/mL of each of the pBMP2/NPs or pDMP1/NPs preserved high levels of cell viability, evidenced by live/dead staining in vitro and caused no adverse reactions after implantation on C57BL6 mice in vivo . HTFD/NPs constructs induced rapid and pronounced odontogenic shift of the DPSCs, as evidenced by relevant gene expression patterns of RunX2, ALP, BGLAP, BMP-2, DMP-1, DSPP by real-time PCR, and acquirement of polarized meta-mitotic phenotype with cellular protrusions entering the dentinal tubules as visualized by scanning electron microscopy. Taken together, HTFD/NPs constitute a promising tool for customized reconstruction of the ortho-dentin/odontoblastic layer barrier and preservation of pulp vitality. Statement of significance: In clinical dentistry, the most common therapeutic approach for the reconstruction of hard dental tissue defects is the replacement by resin-based restorative materials. Even modern bioactive materials focus on reparative dentinogenesis, leading to amorphous dentin-bridge formation in proximity to the pulp. Therefore, the natural microarchitecture of tubular ortho-dentin is not recapitulated, and the sensory and defensive role of odontoblasts is sidelined. This study approaches the reconstruction at the dentin-pulp interface using a construct of human treated dentin (HTFD) scaffold and plasmid-carrying nanoparticles (NPs) encoding dentinogenic factors (DMP-1 or BMP-2) with excellent in vitro and in vivo properties. As a future perspective, the HTFD/NPs constructs could act as bio-fillings for personalized reconstruction of the dentin-pulp interface. Graphical abstract: Image, graphical abstract